Small Universal Circular Post Machines - Manfred Kudlek; Yurii Rogozhin (Computer Science Journal of Moldova, 2001)
We consider a new kind of machines with a circular tape and moving in one direction only, so-called Circular Post machines. Using 2-tag systems we construct some small universal machines of this kind.